Pathogenicity and virulence of Marburg virus. Issue 1 (31st December 2022) - Abir, Mehedy Hasan; Rahman, Tanjilur; Das, Ayan; Etu, Silvia Naznin; Nafiz, Iqbal Hossain; Rakib, Ahmed; Mitra, Saikat; Emran, Talha Bin; Dhama, Kuldeep; Islam, Ariful; Siyadatpanah, Abolghasem; Mahmud, Shafi; et al.
ABSTRACT: Marburg virus (MARV) has been a major concern since 1967, with two major outbreaks occurring in 1998 and 2004. Infection from MARV results in severe hemorrhagic fever, causing organ dysfunction and death. Exposure to fruit bats in caves and mines, and human-to-human transmission had major roles in the amplification of MARV outbreaks in African countries. The high fatality rate of up to 90% demands the broad study of MARV diseases (MVD) that correspond with MARV infection. Since large outbreaks are rare for MARV, clinical investigations are often inadequate for providing the substantial data necessary to determine the treatment of MARV disease. Therefore, an overall review may contribute to minimizing the limitations associated with future medical research and improve the clinical management of MVD. In this review, we sought to analyze and amalgamate significant information regarding MARV disease epidemics, pathophysiology, and management approaches to provide a better understanding of this deadly virus and the associated infection.